Strategic management accounting practices in business: A systematic review of the literature and future research directions - Nik Herda Nik Abdullah; Shamala Krishnan; Azliza Azrah Mohd Zakaria; Grace Morris (Cogent Business & Management, 2022)
In the last decade, strategic management accounting (SMA) practices have garnered considerable attention from academics and business organizations. SMA is described as the provision and analysis of management accounting data on a company's product in the markets, its cost structure, and competitors' costs, as well as the monitoring of the firm's and its competitors' strategic positions in these markets over time. SMA techniques have the potential to provide a wide range of benefits for organizations. These techniques include competitor accounting, customer accounting, strategic costing, strategic planning, control and performance management, and strategic decision making. Despite the high potential of SMA for decision making, there are still issues with practical application and a lack of knowledge about using SMA strategically to achieve business goals. Using a systematic literature review approach, the present study aims to provide a critical literature review to identify the motivation to adopt SMA practices; to identify evidence on the usage of SMA practices; to provide a synthesis of the impacts of SMA on business goals, and to identify the knowledge gaps that exist in the current literature about SMA practices and business goals, highlighting the potential benefits, challenges, and opportunities, and presenting a discussion about future research directions. The review's main contributions are to provide an in-depth discussion of the peer-reviewed literature in which the term SMA is used, as well as a basis for future research and practice.
Keywords: 650; competitor analysis; Costing; customer analysis; performance measurement; strategic management accounting